2022
DOI: 10.4102/hsag.v27i0.2081
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, beliefs and intentions of African men in the Free State about prostate cancer screening

Abstract: Background: African men are less likely to participate in prostate cancer (PCa) screening, which may be beneficial to some of them. Gaps in knowledge, cultural factors and beliefs are associated with their screening intentions.Aim: To determine the knowledge, cultural factors and screening intentions of African males regarding PCa screening.Setting: The study was conducted among African men attending randomly selected primary healthcare clinics in the Free State province.Methods: An analytical, cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Similarly, this study found a negative relationship between general health‐related anxiety and PSA testing, but only in those who had visited their GP less than twice in the previous 12 months. Another study found a negative relationship between fear of the procedure (PSA or DRE) and screening intention in a sample of 389 men living in South Africa 94 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, this study found a negative relationship between general health‐related anxiety and PSA testing, but only in those who had visited their GP less than twice in the previous 12 months. Another study found a negative relationship between fear of the procedure (PSA or DRE) and screening intention in a sample of 389 men living in South Africa 94 …”
Section: Resultsmentioning
confidence: 99%
“…Eight relationships between anticipatory anxiety constructs and screening behaviour were tested across six studies focussed on screening for prostate cancer via a Prostate Specific Antigen (PSA) test, 41,73,[92][93][94][95] one in combination with digital rectal examination (DRE). 94…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation